Characterization of Household Waste in Islamabad and Exploring Possible Reuse and Recycling Options - Qasim, Muhammad; Anjum, Nomana; Iftikhar, Nazia; Manzar, Saima; Baber, Shaista (Nurture, 2011)
Increased solid waste generation creates additional environmental problems as many cities are unable to manage it. Unfortunately, none of the cities of Pakistan has a proper solid waste management system right from collection of waste up to its proper disposal. Islamabad, being a capital city of Pakistan with 90% literacy rate faces the similar solid waste management problems. In Islamabad around 91% of total municipal waste is composed of green and household waste which may support composting. Currently, there is no proper sorting system of municipal solid waste which indicates insufficient and inefficient recycling of organic/inorganic waste materials in Islamabad. The major portion of the recyclable household waste collected is gone wasted and buried at dumping sites in sectors H-12 and H-10. The paper is an initiative to determine reusable components of household solid waste in Islamabad and explore possible recycling/reuse options. By adopting stratified random sampling design, the primary research is carried out in sector G-7, Islamabad. Districts with in the sector have been made on the basis of income groups. 2% sample size is taken as waste generated within the income groups has high degree of similarity. The study concluded the possible reuse and recycling options for the major household waste in Islamabad.